Visual Schedule towards the Decline of Behavioral Problems in Feeding Activities and Defecation in Children with Autism - Siyoto, Sandu (Jurnal NERS, 2015)
Introduction: Autism is a pervasive developmental disorder in children that is characterized by the disruption and delays in cognitive, language, behavior, communication and social interaction. One of the ways for children with autism is the visual schedule. Visual schedule is a learning method in the form of information in a visual form that communicates a series of activities. This study aimed to determine the effects of a visual schedule to decrease problem behaviors when feeding activity and defecation in children with autism in the Foundation Board of Christian Education Wetan Jawi (YBPK) Kediri. Method: Research design was One Group Pre Post Test Design, with a population of 30 respondents, used the purposive sampling technique obtained a sample of 16 respondents. When the reseachon April 16 Until Mei 17, 2014. Results: The results showed obtained Asymp significant p = 0.011 <0.05 with Wilcoxon statistical test, which means that HO was rejected and H1 accepted schedule. It means there were visual effects on reducing behavioral problems in feeding activity and defecation in children with autism in the Foundation Board of Christian Education Wetan Jawi (YBPK) Kediri in 2014. Discussion: The Visual schedules can be applied in the treatment of autistic children who have behavior problems, because these techniques can provide influence on autistic children to be able to decrease behavior problems. Keywords: Visual Schedule, decline in behavior problems, children with autism